Ionic polymer interface doping material as well as preparation method and application thereof

By preparing ionic polymer interface doped materials, the problems of energy level mismatch and poor contact at the interface in organic solar cells were solved, the charge extraction and transport efficiency was improved, and the device performance was enhanced.

CN120965976AActive Publication Date: 2025-11-18JIANGHAN UNIVERSITY
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202511501038.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-21
Publication Date
2025-11-18
Estimated Expiration
2045-10-21

AI Technical Summary

Technical Problem

In existing organic solar cells, there is energy level mismatch and poor interfacial contact at the interface between the photoactive layer and the charge transport layer, which leads to low charge extraction efficiency and increased charge accumulation, affecting device performance.

Method used

Ionic polymer interface doping materials are used to prepare compounds through Stille coupling reaction, nucleophilic substitution reaction and polymerization reaction to form compounds with excellent cathode interface doping performance, enhance charge mobility, and mix with perylene diimide-based polymers to form an active layer, thereby optimizing interfacial interactions.

Benefits of technology

It improves the photovoltaic performance of organic solar cells, enhances charge extraction and transport efficiency, reduces non-radiative voltage loss, promotes exciton dissociation and suppresses charge recombination, and achieves more efficient carrier transport.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120965976A_ABST
    Figure CN120965976A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of organic photoelectric materials, and particularly discloses an ionic polymer interface doped material and a preparation method and application thereof. The ionic polymer interface doping material provided by the invention has the structural formula I shown in the formula I, after being ionized, the ionic polymer interface doping material is doped into a cathode interface layer, Br ions can be split out, form new chemical bonds with Ag and absorb additional electric dipoles, the direction of the Br ions is the same as that of an electric dipole of nitrogen-containing CIL, and the formed double dipoles can reduce WF and improve the performance of the cathode. Dark current leakage is inhibited, charge extraction is improved, and JSC and FF are enhanced. In addition, formation of a good phase separation morphology and a high-purity structural domain can be promoted, construction of a high-quality interpenetrating network is facilitated, more efficient and more balanced carrier transport is achieved, dissociation of excitons is effectively promoted, and charge recombination is inhibited. Meanwhile, the interface interaction is enhanced, the charge transmission path is optimized, the electron transport performance is enhanced, and the non-radiation voltage loss is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of organic optoelectronic materials, and particularly relates to an ionic polymer interfacial doping material and a preparation method and application thereof. BACKGROUND

[0002] Although the power conversion efficiency of organic solar cells has been greatly improved, the non-radiative recombination loss at the interface between the photoactive layer and the charge transport layer is still a key bottleneck, which usually limits the open-circuit voltage (Voc) V OC ) and the fill factor (FF) FF ). In particular, the energy level mismatch and poor interface contact at the cathode interlayer (CIL) / active layer junction lead to low charge extraction efficiency and increased charge accumulation, ultimately reducing the device performance. CIL is one of the key factors to achieve high performance and stability of OSC, which can provide energy level alignment at the electrode interface and provide interface dipoles for ohmic contact, effectively reducing the work function (WF) of the cathode, thus promoting efficient electron transfer and collection. Based on these advantages, interface engineering has attracted more and more attention, and recent progress in interface engineering has actually been proven to be an effective method to further improve the PCE and long-term stability of OSC. A suitable interlayer plays a crucial role in constructing various devices based on a given active layer, such as conventional, inverted, semi-transparent and tandem devices. So far, PDINN has become a benchmark for CIL materials due to its inherent advantages such as simple synthesis, clear molecular structure, high electron affinity, and high electron mobility, which has greatly improved the performance of OSC. The wide rigid π-conjugated backbone of PDINN will lead to self-aggregation of ETL, making the film-forming quality of ETL on the active layer still insufficient, and it is difficult to form a tight contact with the active layer and the metal electrode. The non-uniformity of ETL has a great influence on the charge extraction process, and these defects may cause serious leakage current, thereby affecting the performance of the device.

[0003] Therefore, how to modify the benchmark CIL to solve the problems of energy level mismatch, poor interface contact and poor film-forming quality of ETL at the CIL / active layer junction, so as to further improve the power conversion efficiency and long-term stability of organic solar cells, is a technical problem to be solved. SUMMARY

[0004] The present application aims at the above-mentioned deficiencies in the prior art, and provides an ionic polymer interfacial doping material and a preparation method and application thereof. The ionic polymer interfacial doping material has excellent cathode interfacial doping performance, good intermolecular stacking effect, and helps to improve the charge mobility, and has better photovoltaic performance in the test of the three organic solar cells.

[0005] The first object of the present application is to provide an ionic polymer interfacial doping material, the structural formula of which is shown as formula I. wherein n is a natural number of 9-15.

[0006] The second object of the present application is to provide a preparation method of the ionic polymer interfacial doping material, characterized by comprising the following steps: S1, obtaining compound 4 by Stille coupling reaction with 4,7-dibromo-2-(6-bromohexyl)-2H-benzotriazole and 2-tributylstannylthiophene as raw materials; ; S2, obtaining compound 5 by bromination of compound 4 with N-bromosuccinimide; ; S3, obtaining compound 6 by nucleophilic substitution of piperidine with compound 5 in the presence of potassium carbonate; ; S4, obtaining compound 7 by polymerization reaction of compound 6 with 2,5-bis(trimethylstannyl)thiophene under the action of tetrakis(triphenylphosphine)palladium catalyst; ; S5, obtaining the compound with the structural formula shown as formula I by ionization reaction of compound 7 with bromoethane.

[0007] Further, in step S1, the molar ratio of 4,7-dibromo-2-(6-bromohexyl)-2H-benzotriazole to 2-tributylstannylthiophene is 1: (2-4), and the molar ratio of 4,7-dibromo-2-(6-bromohexyl)-2H-benzotriazole to tetrakis(triphenylphosphine)palladium is 1: (0.05-0.1).

[0008] Further, in step S2, the molar ratio of compound 4 to N-bromosuccinimide is 1: (2-3).

[0009] Further, in step S3, the molar ratio of compound 5 to piperidine is 1: (1-3), and the molar ratio of compound 5 to potassium carbonate is 1: (2-3).

[0010] Further, in step S4, the molar ratio of compound 6 to 2,5-bis(trimethylstannyl)thiophene is 1: (1-1.2), and the molar ratio of compound 6 to tetrakis(triphenylphosphine)palladium is 1: (0.05-0.1).

[0011] Further, in step S4, the mass-volume ratio of compound 7 to bromoethane is 0.05 g: (1-2) mL.

[0012] A third objective of the present invention is to provide an active layer for an organic solar cell, the active layer comprising a first layer and a second layer disposed on the surface of the first layer, the first layer being a mixture of an electron donor material and an electron acceptor material, and the second layer being a mixture of a perylene diimide-based polymer and an ionic polymer interface doping material of the present invention.

[0013] Furthermore, the mass percentage of the ionic polymer interface doped material is 0.25 to 1% of the perylene diimide-based polymer.

[0014] A fourth objective of this invention is to provide the application of the above-mentioned ionic polymer interface doping material or the active layer of an organic solar cell in the fabrication of organic solar cell devices.

[0015] Compared with the prior art, the present invention has the following beneficial effects: (1) The ionic piperidine polymer doped material provided by this invention can achieve synergistic control of the phase separation morphology and photophysical processes of blended films. After ionization, the ionic piperidine polymer doped material is doped into the cathode interface layer. Br ions can be cleaved from PIP, form new chemical bonds with Ag, and absorb additional electric dipoles, the direction of which is the same as the electric dipole direction of nitrogen-containing CILs. Since the double dipoles can reduce WF, suppress dark current leakage, and improve charge extraction, they can enhance the... J SC And FF. This ionic piperidine polymer doped material can also promote the formation of good phase separation morphology and high-purity structural domains, which is beneficial for constructing high-quality interpenetrating networks, achieving more efficient and balanced charge carrier transport, effectively promoting exciton dissociation and suppressing charge recombination. At the same time, it enhances interfacial interactions, optimizes charge transport paths, enhances electron transport performance, and reduces nonradiative voltage loss.

[0016] (2) The novel ionic polymer designed by the present invention through structure is a key way to achieve synergistic control of nanoscale phase separation morphology and photophysical process, thereby enabling the preparation of high-efficiency organic solar cells.

[0017] (3) The synthesis process provided by the present invention is simple and easy to purify, and has good prospects for practical application. Attached Figure Description

[0018] Figure 1 A process flow diagram for preparing an ionic polymer interface doped material provided by the present invention; Figure 2 Compound 3 prepared in this invention 1 H NMR spectrum; Figure 3 Compound 4 prepared in this invention1 H NMR spectrum; Figure 4 Compound 5 prepared in this invention 1 H NMR spectrum; Figure 5 Compound 6 prepared in this invention 1 H NMR spectrum; Figure 6 The LC-MS spectrum of compound 6 prepared in this invention; Figure 7 The current density-voltage ratio of the organic solar energy device prepared for this invention J-V )test; Figure 8 The external quantum efficiency (EQE) test results of the organic solar energy device prepared in this invention are shown. Figure 9 The image shows the ultraviolet-visible spectrum of the organic solar energy device prepared according to the present invention. Figure 10 The electrochemical test results are for the organic solar energy device prepared according to the present invention; Figure 11 This is a test image from an atomic force microscope; Figure 12 This is a UV-Vis absorption spectrum. Figure 13 The thermogravimetric analysis results are for the ionic polymer interface doped material prepared in this invention. Detailed Implementation

[0019] To more clearly explain the technical solution and beneficial effects of the present invention, the present invention will be described in detail below with reference to the accompanying drawings and embodiments. It should be noted that the described accompanying drawings are only some embodiments of the present invention and are used only to explain the present invention, and should not be construed as limiting the present invention. Unless otherwise specified, the equipment and reagents used in the present invention are commercially available products conventional in this technical field.

[0020] The present invention provides an ionic polymer interface doped material with the structural formula shown in Formula I. , where n is a natural number between 9 and 15.

[0021] It can be synthesized from starting material compound 3: 4,7-dibromo-2-(6-bromohexyl)-2H-benzotriazole (CAS No.: 890704-02-6), and the specific process route is as follows: Step 1, under nitrogen protection, compound 3, 2-tributylstannylthiophene and tetrakis triphenylphosphine palladium were added into a flask. Then anhydrous toluene was injected, and the mixture was stirred at 110 °C for 12 hours. Then the mixture was quenched with cold deionized water, and extracted with dichloromethane for three times. The combined organic layer was washed with deionized water for three times, and dried with anhydrous sodium sulfate. After removing the solvent, the crude product was purified by silica gel column chromatography (eluent: petroleum ether: dichloromethane) to obtain compound 4 as a green solid, . Wherein, the molar ratio of compound 3, 2-tributylstannylthiophene is 1: (2-4), preferably 1:3; the molar ratio of compound 3, tetrakis triphenylphosphine palladium is 1: (0.05-0.1), preferably 1:0.08.

[0022] Step 2, compound 4 was dissolved in chloroform, and N-bromosuccinimide was added in batches under light protection. Stirring at room temperature for 4 hours. Subsequently, the mixture was neutralized with water, and extracted with dichloromethane for three times. The organic layer was combined, washed with deionized water for three times, and then dried with anhydrous sodium sulfate. After removing the solvent, the crude product was purified by silica gel column chromatography (eluent: petroleum ether: dichloromethane) to obtain compound 5 as a light yellow solid, . Wherein, the molar ratio of compound 4 and N-bromosuccinimide is 1: (2-3), preferably 1:2.5.

[0023] Step 3, compound 5 was dissolved in dimethylformamide (DMF), and potassium carbonate was added. Heating and stirring to 80 °C, then adding piperidine, and continuing to react for two hours. The reaction was poured into water, and extracted with ethyl acetate for three times. The organic layer was washed with water, and then dried with anhydrous sodium sulfate. After removing the solvent, the crude product was purified by silica gel column chromatography (eluent: petroleum ether: ethyl acetate) to obtain compound 6 as a yellow solid, . Wherein, the molar ratio of compound 5 and piperidine is 1: (1-3), preferably 1:2; the molar ratio of compound 5 and potassium carbonate is 1: (2-3), preferably 1:2.

[0024] Step 4, compound 6, 2,5-bis (trimethylstannyl) thiophene, tetrakis triphenylphosphine palladium were added into anhydrous toluene under nitrogen atmosphere. The reaction mixture was stirred at 110 °C for 12 hours. The reaction was poured into methanol to form a precipitate. Then the precipitate was washed with methanol and n-hexane in sequence. The precipitate was collected and dried under vacuum at room temperature to obtain compound 7, , wherein the molar ratio of compound 6 and 2,5-bis(trimethylstannyl)thiophene is 1:(1~1.2), preferably 1:1; the molar ratio of compound 6 and 2,5-bis(trimethylstannyl)thiophene is 1:(1~1.2), preferably 1:1.

[0025] It should be noted that the starting material can be commercially available, and can also be synthesized by itself, and in the present application, 3,6-dibromo-1,2-phenylenediamine (CAS:69272-50-0) is used for synthesis, specifically: Under a nitrogen (N2) atmosphere, 3,6-dibromo-1,2-phenylenediamine is dissolved in acetic acid, stirred at room temperature (RT) for 20 minutes, then sodium nitrite is dissolved in water and slowly added in batches. Stir for 8 hours at room temperature. Pour the reaction into water, extract with dichloromethane three times. The organic layer is washed with water and then dried over anhydrous sodium sulfate. After removing the solvent, dry in a vacuum oven to obtain compound 2 as a light pink solid, , wherein the molar ratio of 3,6-dibromo-1,2-phenylenediamine and sodium nitrite is 1:(2~4), preferably 1:2.

[0026] Then, compound 2 is dissolved in dimethylformamide, and potassium carbonate is added. Heat and stir to 60 ℃, then add 1,6-dibromohexane and continue to react for two hours. Pour the reaction into water and extract with ethyl acetate three times. The organic layer is washed with water and then dried over anhydrous sodium sulfate. After removing the solvent, the crude product is purified by silica gel column chromatography (eluent: petroleum ether:dichloromethane) to obtain compound 3, 4,7-dibromo-2-(6-bromohexyl)-2H-benzotriazole, as a white solid, , wherein the molar ratio of compound 2 and potassium carbonate is 1:(1~3), preferably 1:2, and the molar ratio of compound 2 and 1,6-dibromoethane is 1:(1~2), preferably 1:1.2.

[0027] The prepared compound 7 is subjected to ionization reaction with bromoethane to obtain a compound represented by formula I, n is a natural number of 9-15, named PIP, which is an alcohol-soluble ionomer. The enhanced interfacial interaction optimizes the charge transport path, enhances the electron transport performance, and reduces the non-radiative voltage loss. Compound PIP is doped into the cathode interfacial material perylene diimide-based polymer such as PDINN to form a good phase separation morphology and a high-purity domain, which is conducive to the construction of high-quality interpenetrating network, realizing more efficient and more balanced carrier transport, effectively promoting the dissociation of excitons and inhibiting charge recombination. It can be completely used for the preparation of organic solar cell devices.

[0028] The compound shown in formula I provided by the application can be obtained by using the preparation method, and the preparation process flow is as shown in formula Figure 1 .

[0029] During the research and use of the embodiments of the application, some positive effects are obtained, and the application has great advantages compared with the prior art. The following content is described in combination with data and graphs of the test process, and specifically includes material synthesis and device preparation.

[0030] In the following examples, unless otherwise specified, the "water" used is deionized water.

[0031] In the following tests of the application, the hydrogen nuclear magnetic resonance spectrum test is performed on the AVANCE NEO 400MHz nuclear magnetic resonance spectrometer of Bruker Company in Germany, the solvent used is deuterated chloroform (CDCl3), and tetramethylsilane (TMS) is used for calibration.

[0032] The liquid chromatography test is performed by using Shimadzu LCMS-2010EV liquid chromatography-mass spectrometer.

[0033] Example 1 The embodiment provides an ionic polymer interfacial doping material and a preparation method, and the specific process is as follows: (1) Synthesis of compound 2: Under a nitrogen (N2) atmosphere, compound 1: 3,6-dibromo-1,2-phenylenediamine (5 g, 18.80 mmol) was dissolved in 50 mL of acetic acid, stirred at room temperature (RT) for 20 minutes, then sodium nitrite (2.60 g, 37.6 mmol) was dissolved in water (15 mL) and slowly added dropwise in batches. Stir at room temperature for 8 hours. Pour the reaction into water, extract with dichloromethane three times. The organic layer is washed with water and then dried over anhydrous sodium sulfate. After removing the solvent, dry in a vacuum oven to obtain compound 2 as a light pink solid. (4.58 g, yield: 88%) (2) Synthesis of compound 3 Compound 2 (4.58 g, 16.54 mmol) was dissolved in 50 mL of dimethylformamide (DMF) and potassium carbonate (4.57 g, 33.08 mmol) was added. Heat and stir to 60 °C, then add 1,6-dibromohexane (6.05 g, 24.81 mmol) and continue to react for two hours. Pour the reaction into water and extract with ethyl acetate three times. The organic layer is washed with water and then dried over anhydrous sodium sulfate. After removing the solvent, the crude product is purified by silica gel column chromatography (eluent: petroleum ether: dichloromethane) to obtain white solid compound 3. (2.11 g, 30%). 1H NMR (400 MHz, CDC13) δ (ppm): 7.45 (s, 2H), 4.79 (s, 2H), 3.39 (s, 2H), 2.17 (s, 2H), 1.86 (s, 2H), 1.46 (d, 4H). Compound 3 1 H NMR as Figure 2 shown.

[0034] (3) Synthesis of compound 4 Compound 3 (2.11 g, 4.95 mmol), tributyl(thiophene-2-yl)stannane (4.62 g, 12.38 mmol) and Pd(PPh3)4(100 mg) were added into a flask under nitrogen protection. Then toluene (30 mL) was injected and the mixture was stirred at 110 °C for 12 h. Then the mixture was quenched with cold DI water and extracted with dichloromethane for three times. The combined organic layer was washed with DI water for three times and dried over anhydrous sodium sulfate. After removal of the solvent, the crude product was purified by silica gel column chromatography (eluent: petroleum ether:dichloromethane) to give compound 4 as a green solid. (1.57 g, 71% yield for this step). 1 H NMR (400 MHz, CDC13) δ (ppm): 8.09 (t, 2H), 7.64 (d, 2H), 7.39 (d, 2H), 7.19 (p, 2H), 4.84 (td, 2H), 3.40 (td, 2H), 2.29-2.17 (m, 2H), 1.88 (tq, 2H), 1.52-1.15 (m, 4H). Compound 4 1 H NMR spectrum as Figure 3 shown.

[0035] (4) Synthesis of compound 5 Compound 4 (1.57 g, 3.53 mmol) was dissolved in 20 mL of chloroform and N-bromosuccinimide (1.64 g, 9.19 mmol) was added portionwise under dark condition. It was stirred at room temperature for 4 h. Subsequently, the mixture was neutralized with water and extracted with dichloromethane for three times. The organic layer was combined, washed with DI water for three times and then dried over anhydrous sodium sulfate. After removal of the solvent, the crude product was purified by silica gel column chromatography (eluent: petroleum ether:dichloromethane) to give compound 5 as a light yellow solid. (1.78 g, 84% yield for this step). 1H NMR (400 MHz, CDC13) δ (ppm): 7.85-7.73 (m, 2H), 7.64-7.44 (m, 2H), 7.17-7.09 (m, 2H), 4.81 (q, 2H), 3.41 (td, 2H), 2.21 (p, 2H), 1.87 (q, 2H), 1.49-1.17 (m, 4H). Compound 5 1 H NMR spectrum as Figure 4 shown.

[0036] (5) Synthesis of compound 6 Compound 5 (1.78 g, 2.95 mmol) was dissolved in 20 mL of dimethylformamide (DMF) and potassium carbonate (0.82 g, 5.9 mmol) was added. The reaction was heated and stirred to 80°C, then piperidine (0.50 g, 5.9 mmol) was added and the reaction was continued for two hours. The reaction was poured into water and extracted with ethyl acetate three times. The organic layer was washed with water and then dried over anhydrous sodium sulfate. After removing the solvent, the crude product was purified by silica gel column chromatography (eluent: petroleum ether: ethyl acetate) to obtain compound 6 as a yellow solid. (1.54 g, 86% yield for this step). 1 H NMR (400 MHz, CDC13) δ (ppm): 7.85-7.73 (m, 2H), 7.64-7.44 (m, 2H), 7.17-7.09 (m, 2H), 4.81 (q, 2H), 3.41 (td, 2H), 2.21 (p, 2H), 1.87 (q, 2H), 1.49-1.17 (m, 4H). Compound 5 1 H NMR spectrum as Figure 5 shown, LC-MS spectrum as Figure 6 shown.

[0037] (6) Synthesis of compound 7 Compound 6 (60.85 mg, 0.1 mmol) and 2,5-bis(trimethylstannyl)thiophene (40.98 mg, 0.1 mmol), Pd(PPh3)4(5 mg) were added to anhydrous toluene (5 mL) under a nitrogen atmosphere. The reaction mixture was stirred at 110°C for 12 hours. The reaction was poured into methanol to form a precipitate. The precipitate was then washed with methanol and n-hexane in this order. The precipitate was collected and dried under vacuum at room temperature.

[0038] (7) Synthesis of compound PIP Dissolve 50 mg of compound 7 in a mixed solvent of 15 mL of toluene and 15 mL of methanol, then add 1 mL of bromoethane. Stir the mixture at 60°C for 24 hours. After the reaction is completed, concentrate the reaction solution and precipitate it in n-hexane. Collect the solid and dry it under vacuum for 12 hours. The resulting polymer is characterized as follows: The molecular weight characterization data are as follows: the weight average molecular weight is 5843 Da, the number average molecular weight is 10016 Da, and the polymer molecular weight distribution index is 1.71; as shown in Figure 13 the mass of PIP at a temperature of 265.5°C is 95% of the original, as shown in Figure 12 PIP exhibits a wide absorption in the range of 400-650 nm, with a maximum absorption peak at 497 nm.

[0039] Example 2 The present embodiment provides a small-molecule organic solar cell device.

[0040] The organic solar cell device includes an ITO substrate, a PEDOT:PSS layer, an active layer, an electron transport layer, and an electrode which are sequentially stacked, and the specific preparation process is as follows: (1) After the ITO glass (indium tin oxide conductive glass) is cleaned by ultrasonic wave, it is treated by oxygen-plasma. PEDOT:PSS poly(3,4-ethylenedioxythiophene):poly(styrenesulfonic acid) (Xi'an Yurui Solar Energy Technology Co., Ltd., PEDOT:PSS AI4083, product number: 306020, a mixed solution prepared when purchased) is spin-coated on the ITO at 5000 rpm, and annealed at 150°C for 15 minutes to obtain a substrate with a surface film thickness of about 40 nm.

[0041] (2) Then, the donor material D18 and the acceptor L8-BO (the structural formula is shown below) are mixed as a binary organic solar device (the mass ratio of the donor material and the acceptor material and the additive is preferably 1:1:1), and diiodomethane-trichloromethane mixed solvent (the volume ratio of diiodomethane to trichloromethane is 0.3 μL:100 μL) is added, to prepare a blended solution (the total concentration of the donor and the acceptor is 20 mg / mL). The blended solution is spin-coated on the substrate of step (1) to form a film with a thickness of about 130 nm on the surface of the substrate.

[0042] (3) The substrate obtained in step (2) is placed in a 60 nm culture dish, then 60 μL of chlorobenzene is evenly applied on the surface, followed by solvent vapor annealing (85°C, 5 min), next, an electron transport layer PDINN film is coated on the above active layer using a spin coating speed of 3000 rpm, a PDINN+PIP film (the mass ratio of PDINN:PIP is preferably (1:0.005), and the film thickness is about 10 nm. Finally, a 100 nm thick silver layer is deposited on the electron transport layer by evaporation.

[0043] The specific solar cell efficiency is shown in Table 1 (the equipment used in the laboratory of the present application is a solar simulator, calibrated with a silicon solar cell, and all tests are measured under 1 simulated sunlight, 100 mW / cm 2 ).

[0044] ; ; .

[0045] As can be seen from the data in Table 1, the compound PIP prepared in the present application is used as a doping material in PDINN, and the photoelectric conversion efficiency of the binary photovoltaic device, this kind of polymer doping material has a unique advantage in the commercialization of organic solar cells.

[0046] Table 1. Photovoltaic parameters of the best performance of devices with different ratios of PIP doped PDINN.

[0047]

[0048] Note: V OC is the open circuit voltage, J SC is the short circuit current density, FF is the fill factor, PCE is the functional conversion efficiency.

[0049] The donor D18 and the acceptor L8-BO are mixed as a binary organic solar device (the mass ratio of the donor to the acceptor material and the additive is preferably 1:1:1), and then PIP prepared in Example 1 is doped into the PDINN binary device to prepare an organic solar device (the mass ratio of PDINN:PIP is preferably 1:0.005), and PDINN:PIP is 1:0, 1:0.0025, 1:0.0075, 1:0.01 as a comparison group, then the J-V curve is measured under 1 simulated sunlight (SAN-EI, XES-40S2-CE) 100 mW / cm 2The current-voltage (J-V) characteristics were measured using a Keithley 2450 source meter under the illumination intensity of AM 1.5G).

[0050] The results are shown in FIG. 1, from which it can be seen that the performance of the compound PIP doped PDINN prepared by the application is obviously improved compared with PDINN. In photodynamics, it can be analyzed that the device of the compound PIP doped PDINN has a larger exciton diffusion coefficient and a faster exciton dissociation process compared with the device based on PDINN. Figure 7 As shown in FIG. 2, it is an external quantum efficiency (EQE) test graph: EQE spectra were analyzed using a certified Newport IPCE measurement system. High-sensitivity EQE was measured by using an integrated system (PECT-600, Enlitech), in which the photocurrent was amplified and modulated by a lock-in instrument. Through this test, it is proved that the EQE spectrum of the PIP doped PDINN device is consistent with the integral of the solar spectrum (AM 1.5G) compared with the PDINN device

[0051] Figure 8 As shown in FIG. 3, it is a UV-Vis spectrum test graph: the UV-Vis absorption spectra of the solution and the thin film were recorded by a Hitachi U-4100 spectrophotometer. The optical absorption spectrum of the thin film was prepared by spin coating the methanol solution (1.0 mg / mL, 1500 rpm) onto a quartz plate. The UV-Vis absorption spectra of PDINN, PDINN+0.25% PIP, PDINN+0.50% PIP, PDINN+0.75% PIP and PDINN+1.00% PIP were tested by using a UV spectrophotometer. It can be seen that PIP shows strong absorption in the range of 400-600 nm. J As shown in FIG. 4, it is an electrochemical test result: using a three-electrode system (a glassy carbon electrode as a working electrode, an Ag / Ag + electrode as a reference electrode and a platinum wire counter electrode) on a CHI660D electrochemical workstation, using a nitrogen-saturated solution of 0.1 mol / L tetrabutylammonium hexafluorophosphate in acetonitrile as an electrolyte, using a scan rate of 100 mV / s for cyclic voltammetry (CV) measurement, using ferrocene-ferrocenium salt (Fc / Fc + ) as an internal standard, and the absolute energy compared with vacuum is -4.8 eV. The HOMO and LUMO energy levels of the material are determined according to the equation:

[0052] Figure 9 As shown in FIG. 5, it is a UV-Vis spectrum test graph: the UV-Vis absorption spectra of the solution and the thin film were recorded by a Hitachi U-4100 spectrophotometer. The optical absorption spectrum of the thin film was prepared by spin coating the methanol solution (1.0 mg / mL, 1500 rpm) onto a quartz plate. The UV-Vis absorption spectra of PDINN, PDINN+0.25% PIP, PDINN+0.50% PIP, PDINN+0.75% PIP and PDINN+1.00% PIP were tested by using a UV spectrophotometer. It can be seen that PIP shows strong absorption in the range of 400-600 nm. Figure 10 As shown in FIG. 6, it is an electrochemical test result: using a three-electrode system (a glassy carbon electrode as a working electrode, an Ag / Ag + electrode as a reference electrode and a platinum wire counter electrode) on a CHI660D electrochemical workstation, using a nitrogen-saturated solution of 0.1 mol / L tetrabutylammonium hexafluorophosphate in acetonitrile as an electrolyte, using a scan rate of 100 mV / s for cyclic voltammetry (CV) measurement, using ferrocene-ferrocenium salt (Fc / Fc + ) as an internal standard, and the absolute energy compared with vacuum is -4.8 eV. The HOMO and LUMO energy levels of the material are determined according to the equation:

[0053] Measurements were taken using the cyclic voltammetry method, such as... Figure 10 As shown, for PDINN, the highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO) levels are -5.8 eV and -3.83 eV, respectively. For PIP, the highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO) levels are -5.83 eV and -3.92 eV, respectively.

[0054] like Figure 11 The image shown is an atomic force microscope (AFM) image: the film morphology was measured using a Park NX10 AFM. The image shows the R values ​​for PDINN, PDINN+0.25%PIP, PDINN+0.50%PIP, PDINN+0.75%, and PDINN+1.00%PIP. q The values ​​were 2.51 nm, 2.36 nm, 2.07 nm, 2.12 nm, and 2.50 nm, respectively. PDINN+0.50%PIP had the lowest surface roughness, which indicates that the flat and uniform surface of the PDINN+0.50%PIP film promotes excellent physical and electronic contact between the ETL and the active layer, thereby reducing interface defects and suppressing interfacial charge recombination.

[0055] like Figure 12 The image shows the UV-Vis absorption spectra of PDINN, PIP, and mixed cathode interlayers with different PDINN:PIP ratios. PIP exhibits broad absorption in the 400-650 nm range, with a maximum absorption peak at 497 nm, which is a 20 nm redshift compared to PDINN, whose maximum absorption peak is at 477 nm.

[0056] For any points not covered above, existing technologies shall apply.

[0057] Although specific embodiments of the present invention have been described in detail by way of examples, those skilled in the art should understand that the above examples are for illustrative purposes only and are not intended to limit the scope of the invention. Those skilled in the art can make various modifications or additions to the described specific embodiments or use similar methods to replace them, without departing from the direction of the invention or exceeding the scope defined by the appended claims. Those skilled in the art should understand that any modifications, equivalent substitutions, improvements, etc., made to the above embodiments based on the technical essence of the present invention should be included within the protection scope of the present invention.

Claims

1. An ionic polymeric interfacial doping material, characterized in that, The structure of the ionic polymer interfacial doping material is shown as formula I: Formula I, wherein n is a natural number of 9-15.

2. A method of preparing the ionic polymeric interfacial doping material of claim 1, characterized by, The method comprises the following steps: S1, obtaining compound 4 by Stille coupling reaction with 4,7-dibromo-2-(6-bromohexyl)-2H-benzotriazole and 2-tributylstannylthiophene as raw materials; ; S2, obtaining compound 5 by bromination of compound 4 with N-bromosuccinimide; ; S3, obtaining compound 6 by nucleophilic substitution of piperidine with compound 5 in the presence of potassium carbonate; ; S4, obtaining compound 7 by polymerization reaction of compound 6 with 2,5-bis(trimethylstannyl)thiophene under the action of tetrakis(triphenylphosphine)palladium catalyst; ; S5, obtaining a compound with the structure shown as formula I by ionization reaction of compound 7 with bromoethane.

3. The preparation method according to claim 2, characterized in that, In step S1, the molar ratio of 4,7-dibromo-2-(6-bromohexyl)-2H-benzotriazole to 2-tributylstannylthiophene is 1: (2-4), and the molar ratio of 4,7-dibromo-2-(6-bromohexyl)-2H-benzotriazole to tetrakis(triphenylphosphine)palladium is 1: (0.05-0.1).

4. The production method according to claim 2, characterized by, In step S2, the molar ratio of compound 4 to N-bromosuccinimide is 1: (2-3).

5. The preparation method according to claim 2, characterized in that, In step S3, the molar ratio of compound 5 to piperidine is 1: (1-3), and the molar ratio of compound 5 to potassium carbonate is 1: (2-3).

6. The preparation method according to claim 2, characterized in that, In step S4, the molar ratio of compound 6 to 2,5-bis(trimethylstannyl)thiophene is 1: (1-1.2), and the molar ratio of compound 6 to tetrakis(triphenylphosphine)palladium is 1: (0.05-0.1).

7. The preparation method according to claim 2, characterized in that, In step S4, the mass-volume ratio of compound 7 to bromoethane is 0.05 g: (1-2) mL.

8. An active layer of an organic solar cell, characterized in that The active layer comprises a first layer and a second layer arranged on the surface of the first layer, the first layer is a mixture of electron donor material and electron acceptor material, and the second layer is a mixture of perylenediimide-based polymer and the ionic polymer interfacial doping material of claim 1.

9. The active layer of an organic solar cell according to claim 8, wherein The mass proportion of the ionic polymer interfacial doping material is 0.25-1% of the perylenediimide-based polymer.

10. Use of the ionic polymer interfacial doping material of claim 1 or the active layer of the organic solar cell of any one of claims 8-9 in the preparation of an organic solar cell device.

Citation Information

Patent Citations

  • Synthesis method of N-type conjugated polyelectrolyte based on electron deficiency heterocyclic ring main chain

    CN106883389A

  • Preparation method of hyperbranched conjugate polymer electrolyte cathode interface layer containing quaternium terminal ion groups

    CN110204694A

  • Polyfluorene-based side-chain anion exchange membrane and preparation method thereof

    CN113773472A

  • Anion exchange polymer, anion exchange membrane and preparation method and application thereof

    CN116425958A